2021
DOI: 10.21037/tau-21-329
|View full text |Cite
|
Sign up to set email alerts
|

Whether histologic subtyping affect the oncological outcomes of patients with papillary renal cell carcinoma: evidence from a systematic review and meta-analysis

Abstract: Background: Whether the histologic subtype (type 1 and type 2) of papillary renal cell carcinoma (pRCC) is a tool to predict the prognosis is of great debate. This study is aimed to evaluate the prognostic significance of histologic subtype in patients with pRCC after surgery through a systematic review and meta-analysis.Methods: We searched PubMed, the Web of Science, Cochrane library and EMBASE databases to identify studies published until January 20, 2021 according to the PRISMA (Preferred Reporting Items f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…15 WHO/ISUP nucleolar grade is a validated and currently used histologic parameter for PRCC 12 that provides better prognostication for oncologic outcomes, compared to the traditional histologic subtyping. 9,10,[29][30][31] Although the prognostic significance of WHO/ISUP grade was demonstrated in univariate analysis, we found, however, that WHO/ISUP grade was not significant in predicting survival when controlling for other variables, as already reported. 13,14,31 In the current practice, WHO/ISUP grade still remains a relevant histologic parameter in PRCC and we propose that ABCC2 can be further validated by using it in conjunction with the WHO/ISUP grade in independent PRCC cohorts for more accurate prognostication.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…15 WHO/ISUP nucleolar grade is a validated and currently used histologic parameter for PRCC 12 that provides better prognostication for oncologic outcomes, compared to the traditional histologic subtyping. 9,10,[29][30][31] Although the prognostic significance of WHO/ISUP grade was demonstrated in univariate analysis, we found, however, that WHO/ISUP grade was not significant in predicting survival when controlling for other variables, as already reported. 13,14,31 In the current practice, WHO/ISUP grade still remains a relevant histologic parameter in PRCC and we propose that ABCC2 can be further validated by using it in conjunction with the WHO/ISUP grade in independent PRCC cohorts for more accurate prognostication.…”
Section: Discussionsupporting
confidence: 53%
“…WHO/ISUP nucleolar grade is a validated and currently used histologic parameter for PRCC 12 that provides better prognostication for oncologic outcomes, compared to the traditional histologic subtyping 9,10,29–31 . Although the prognostic significance of WHO/ISUP grade was demonstrated in univariate analysis, we found, however, that WHO/ISUP grade was not significant in predicting survival when controlling for other variables, as already reported 13,14,31 .…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…PRCC can be divided into two different subtypes, type 1 and type 2 (2). The systematic review and meta-analysis by Xiong et al collected a total of 4494 pRCC patients from 22 studies and showed that overall survival and cancer specific survival was worse in type 2 pRCC patients than in type 1 pRCC patients (22). Because the two tumours have many differences in biology, treatment options and prognosis, it is clinically important to distinguish accurately between type 1 and type 2 tumours preoperatively.…”
Section: Discussionmentioning
confidence: 99%